Book & Job Printing Office, Fobes, Hayward, & Co., Confectionary - Sampson, Davenport, & Co. (Tufts Archival Research Center, 2005)
Page image of Book & Job Printing Office, Fobes, Hayward, & Co., Confectionary from the 1870 Boston City Directory